Design, synthesis, and biological evaluation of chalcones for anticancer properties targeting glycogen synthase kinase 3 beta - Ahn, Seunghyun; Truong, Vi Nguyen-Phuong; Kim, Beomsoo; Yoo, Miri; Lim, Yoongho; Cho, Somi Kim; Koh, Dongsoo (Applied biological chemistry, 2022)
Chalcones compounds have been investigated to exhibit anticancer activity through various physiological modes of action. In order to develop chalcone compounds with novel anticancer-related modes of action, diverse chalcone compounds were designed and synthesized. Variously substituted poly-methoxy chalcone compounds 1 – 17 were prepared, and their structures were identified using high-resolution mass spectrometry (HR/MS) and nuclear magnetic resonance (NMR) experiments. Long-term survival clonogenic assay was applied to evaluate their anti-cancer abilities and revealed that their GI50 values ranged between 1.33 and 172.20 μM. When MCF-7SC cells were treated with various concentrations of compound 14 , reduced cell viability and induced apoptosis in MCF-7SC cells were observed in a dose-dependent manner. Wound healing assay demonstrated that compound 14 prevented the MCF7-SC migrated cells at non-lethal concentrations after 12 and 24 h of exposure. The efficiency of compound 14 on the levels of Epithelial-mesenchymal transition (EMT) markers was accessed by the western blot analysis. For the concrete understanding of anticancer properties at the molecular level, in vitro kinase assays on 12 cancer related proteins were carried out. Glycogen synthase kinase 3 beta (GSK3β) was most effectively inhibited by compound 14 with 89% inhibitory activity at 10 µM against GSK3β. The binding mode of compound 14 with GSK3β was reinforced through in silico experiments, which demonstrated compound 14 binds with GSK3β at binding affinity ranged between − 7.5 kcal/mol and − 6.8 kcal/mol. SwissADME analysis provided the druggability and leadlikeness of compound 14 , which unveiled drug development possibilities of chalcone compound 14 .